Crafting lesson studies in initial teacher training: challenges for academic tutoring - Peña-Trapero, Noemí; Rodriguez-Robles, Cristina; Servan-Núñez, María José (My University, 2019)
This paper presents the results of research on Lesson Study's potential to reconstruct student teachers' practical knowledge. It specifically focuses on a Lesson Study implemented as part of the subjects Practicum III and Degree Essay which are imparted in year four of the Degree in Infant Education at Málaga University. The work involves qualitative research that is developed through two case studies. The Lesson Study comprises practice over the course of four months, carried out in schools as part of the Practicum III. Here the first six phases are developed: (1) Define the problem; (2) Design the Experimental Lesson; (3) Develop the first Experimental Lesson; (4) Analyse; (5) Redesign; (6) Develop the second Experimental Lesson. The experience will finish with drafting and defending the Final Dissertation, which makes up phase seven (analysis and presentation in an expanded context). The information collection strategies we used to investigate the chosen case were observation, interview, documentary review and the researchers' diary. All the information collected was analysed and categorised. The results of the research have shown that academic tutoring by university teachers must overcome several key challenges. Specifically, the biggest challenges identified were students' difficulties in cooperative work, and the contrast between their enthusiasm for developing the proposal and their difficulty in bringing it together in a group document. We have identified good practice in academic tutoring: e.g. following up with the group, supporting individual reflection through feedback on the portfolio, creating an atmosphere of trust in which the group can express itself emotionally, offering up questions that guide reflection rather than answers, etc.
Keywords: Educación; Lesson Study; Desarrollo profesional docente; Formación inicial de docentes; Docencia universitaria